Oncolytic Immunotherapy: Dying the Right Way is a Key to Eliciting Potent Antitumor Immunity - Guo, Zong Sheng; Liu, Zuqiang; Bartlett, David L. (Frontiers in Oncology, 2014)
Oncolytic viruses (OVs) are novel immunotherapeutic agents whose anticancer effects come from both oncolysis and elicited antitumor immunity. OVs induce mostly immunogenic cancer cell death (ICD), including immunogenic apoptosis, necrosis/necroptosis, pyroptosis and autophagic cell death, leading to exposure of calreticulin and heat-shock proteins to the cell surface, and/or released ATP, high mobility group box-1 [HMGB1], uric acid, and other DAMPs as well as PAMPs as danger signals, along with tumor-associated antigens, to activate dendritic cells (DCs) and elicit adaptive antitumor immunity. Dying the right way may greatly potentiate adaptive antitumor immunity. The mode of cancer cell death may be modulated by individual OVs and cancer cells as they often encode and express genes that inhibit/promote apoptosis, necroptosis or autophagic cell death. We can genetically engineer OVs with death-pathway-modulating genes and thus skew the infected cancer cells towards certain death pathways for the enhanced immunogenicity. Strategies combining with some standard therapeutic regimens may also change the immunological consequence of cancer cell death. In this review, we discuss recent advances in our understanding of danger signals, modes of cancer cell death induced by OVs, the induced danger signals and functions in eliciting subsequent antitumor immunity. We also discuss potential combination strategies to target cells into specific modes of ICD and enhance cancer immunogenicity, including blockade of immune checkpoints, in order to break immune tolerance, improve antitumor immunity and thus the overall therapeutic efficacy.